Analysis of Compliance Appendectomy Integrated Care Pathway (ICP) and Evaluation of Its Implementation at Awal Bros Batam Hospital Year 2016 - Sari Suciati, S; Yulianty Permanasari, V (KnE Life Sciences, 2018)
Integrated Care Pathway is an integrated service planning concept that uses evidencebased medical service standard aimed at improving service quality. Appendectomy ICP was formed in 2013 at Awal Bros Batam Hospital. This research uses quantitative and qualitative approach based on the seven criteria of Malcolm Baldrige with sequential explanatory method. The criteria and feedback of the Baldrige assessment are based on two dimensions of evaluation – Process and Result dimensions. Four factors were used to evaluate the Process dimension. They are: Approach, Deployment, Learning, and Integration (ADLI); while the four factors used to evaluate the results include Level, Trend, Comparison, and Integration (LeTCI). The result shows that the compliance of ICP implementation decreases the patients’ length of stay (P-value = 0.001). It also derives that there is no relationship with patient outcomes (P-value = 0.318). The discussion of the Problem Tree based on Baldrige criteria indicates that leaders are the first foundation in an organization. They set the vision, mission, and organizational goals. Leaders build the organization’s culture through words, actions, and behaviours. Good leadership can improve strategic planning, focus on workforce, customer focus and organizational performance. Leadership strategies and roles contribute significantly to the implementation of ICP development. In conclusion, the implementation of leadership, strategic planning, workforce focus, customer focus, focus on process, measurement, analysis and knowledge management, and good organizational performance play important role to support the achievement of ICP implementation through Baldrige criteria. Keywords: Integrated Care Pathway (ICP), patient outcomes, Malcolm Baldrige criteria